Mechanisms and context in the San Patrignano drug recovery community, Italy: a qualitative study to inform transfer to Scotland. (2nd January 2021) - Devlin, Alison M.; Wight, Daniel
Abstract: The San Patrignano drug recovery community, Italy, is regarded as one of the most successful in the world. However, if this model is to be transferred to other countries, it is necessary to clarify its underlying mechanisms and how far their success is context dependent. This qualitative study investigated these features of the San Patrignano model. Data collection included semi-structured interviews with six key stakeholders and 10 days' observational field notes. Data were synthesised using frameworks and analysis was informed by realist principles. Individual level mechanisms include: commitment to change, removal from former social environment, communal living, peer mentor with lived experience and meaningful work. These operate in the context of a free of charge, long term (3–4 year) residential community. Organisational level mechanisms are: visionary leadership, staff dedication, social enterprise and adaptable learning. Organisational contextual factors include: a gap in suitable provision for drug recovery and the region's high level of social capital. Articulating the programme theory of the recovery model and its contextual dependency helps clarify which elements should be transferred and how far they need to be adapted for different socio-cultural settings. The recognition of context is crucial when considering transfer of effective complex interventions across countries.